Relationship between parenting style and academic resilience of adolescent students with special reference to Jorhat district, Assam - Saswati Chutia; Jagat Swargiary (Journal of Education and Health Promotion, 2024)
BACKGROUND: Parenting is the most vital and crucial responsibility, although it is often overlooked. Research studies have found that close relationship with parents is associated with the positive development of a child. Academic resilience is one of the key factors forthe positive development of students. “Academic resilience refers to a student’s ability to deal with failure, academic setbacks, and so on”. Several research investigations have shown numerous factors that aid in the promotion of academic resilience among students. Parenting is one of them. Therefore, this study tries to investigate the strength and direction of the relationship between parenting style and academic resilience. MATERIAL AND METHOD: Descriptive survey method has been employed in this study. The study was conducted in three govt. high schools of Jorhat district, Assam, India under the SEBA (Secondary Board of Education). The sample of the present study consists of 101 high school students studying in class X, which include both boys and girls. Data were collected by administering two standardized tools to the sample students. STATISTICAL TECHNIQUE USED: Pearson Product–Moment correlation has been used in this study. RESULT: Results indicate that there a exist significant favorable association between democratic parenting style and academic resilience of adolescent students. It is also found that there exists a low correlation between autocratic parenting style and academic resilienceof adolescent students. The correlation between permissive parenting style and adolescent students’ academic resilience is also very low. Also, it has been found that there exists a low or weak correlation between uninvolved parenting style and academic resilience of adolescent students. CONCLUSION: The findings of this study indicate a statistically significant positive correlation between different parenting styles and the academic resilience of adolescent students. Based on the findings of this study, it is recommended that future research be conducted to investigate whether certain parenting styles can predict the academic resilience of adolescent students.